Proceedings of the 8th International Conference on Tangible, Embedded and Embodied Interaction 2014
DOI: 10.1145/2540930.2540971
|View full text |Cite
|
Sign up to set email alerts
|

jamSheets

Abstract: This works introduces layer jamming as an enabling technology for designing deformable, stiffness-tunable, thin sheet interfaces. Interfaces that exhibit tunable stiffness properties can yield dynamic haptic feedback and shape deformation capabilities. In comparison to the particle jamming, layer jamming allows for constructing thin and lightweight form factors of an interface. We propose five layer structure designs and an approach which composites multiple materials to control the deformability of the interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…However, Ou et al [171] showed that it was also possible to introduce anisotropic deformation using jamming through the structural design of the jammable materials, such as by weaving multiple jamming units into the material, using interleaving flaps in the elastic air bladder, or by introducing crease patterns or cutting geometrical patterns into the jamming flaps [169]. They envisioned that by incorporating more complex weaving patterns or increasing the resolution, it may be possible to program more sophisticated deformation interactions such as the direction of stretching, degree of rolling, bending angle and shear deformation.…”
Section: Anisotropic Structures Within Hcimentioning
confidence: 97%
“…However, Ou et al [171] showed that it was also possible to introduce anisotropic deformation using jamming through the structural design of the jammable materials, such as by weaving multiple jamming units into the material, using interleaving flaps in the elastic air bladder, or by introducing crease patterns or cutting geometrical patterns into the jamming flaps [169]. They envisioned that by incorporating more complex weaving patterns or increasing the resolution, it may be possible to program more sophisticated deformation interactions such as the direction of stretching, degree of rolling, bending angle and shear deformation.…”
Section: Anisotropic Structures Within Hcimentioning
confidence: 97%
“…Instead of melting, friction between plates can also be altered pneumatically. In (27), a number of sheets are inserted into a vacuum bag, which remains extremely flexible until a vacuum is applied and the deformed shape is locked in place. Similarly, particle jamming (53) is a technique where a granular material is encased in a very flexible material.…”
Section: Actuationmentioning
confidence: 99%
“…"Tangible bits" (24) or "radical atoms" (25) promote the idea of presenting information in physical form, not limited to pixels. This concept has found physical implementation in "pushpin computing" (26), which seeks to engineer additional layers of information in everyday objects such as push pins and floor tiles, and a series of works that involve interaction with materials that change their physical properties such as stiffness (27), physical extension (28), or weight (29). As such, these works explore a series of applications as well as their enabling principles, but leave their implementation in systems or products to science and engineering.…”
Section: Introductionmentioning
confidence: 99%
“…It is often used for technical innovation in engineering to increase portability and storage [31]. In HCI, origami has inspired work both practical and playful in nature, such as Lee et al's Foldable Interactive Display [27] where projection is combined with large-scale paper folding to create interactive umbrellas, newspapers and (Alexander, Lucero, & Subramanian, 2012) Variable stiffness deformable user interface for mobile devices, haptic feedback, deformation-based, gestures possible Shape memory alloy (SMA) wires act as actuator and external input sensors MimicTile (Nakagawa, Kamimura, & Kawaguchi, 2012) Copper (its thermo-electric characteristics), polyethylene (high thermal expansion rate) uniMorph ( Digital fabrication of customized thin-film shape-changing interfaces jamSheets (Ou et al, 2014) Technology for designing deformable, stiffness-tunable thin sheet interfaces Sensor layers, multiple materials used in one jamming unit to get different levels of deformation Gummi (Schwesig, Poupyrev, & Mori, 2004) Physical deformation of a hand-held device, bendable device Layers of flexible electronic components including sensors measuring deformation (2D position sensors)…”
Section: Origami In Hcimentioning
confidence: 99%
“…The paper is actuated with SMAs to achieve dramatic movement, design quidelines are given Folding mechanism based on the in-plane contraction of a sheet of shape memory polymer, four shapes are intruduced Shape-changing fashions to employ pneumatically actuated origami, a pneumatic folding, shape-changing skirt Soft-bodied robotic actuators, combines robotics, folding, and fashion Awakened Apparel (Perovich, Mothersill, & Broutin Farah, 2014) Color-Changing Origami (Kaihou, & Wakita, 2013) Color-changing origami using LEDs Uses thermochromic and conductive ink, it can be folded in the same way as paper origami, it mustn't contain any hard electronic components Figure 2. Foldable device analysis, with prototypes listed in alphabetical order: Awakened Apparel [42]; Bookisheet [61]; Colour-Changing Origami [22]; Flexpad [53]; Foldable Interactive Displays [27]; FoldMe [24]; Gummi [49]; jamSheets [40]; MimicTile [33]; PaperFold [11]; PaperTab [56]; PaperWindows [18]; PrintScreen [39]; Projectagami [55]; Shape Memory Alloy [43]; Self-Folding Origami [57]; Sticky Actuator [36]; Tilt Displays [1]; uniMorph [15]; Xpaaand [25];.…”
Section: Animated Papermentioning
confidence: 99%